Design of radio monitoring platform based on VPX open architecture - Lu Chao; Mi Wenlong; Hu Dingrui (Dianzi Jishu Yingyong)
The radio monitoring system puts forward higher requirements for signal search, interception and identification capabilities. The traditional radio monitoring system software and hardware have immature standardization and modularization, strong customization, and poor versatility, and it is difficult to meet future equipment needs. An open radio monitoring system based on VPX combined with the idea of software radio is designed, and the software and hardware architecture of the platform is intensively studied. Finally, a verification platform is built for testing the transmission and system performance, which verifies the feasibility of this platform.